Assessing Computational Thinking Skills: Physics Computational Test based on Scratch Program for High School Students - Ridho Adi Negoro; Wiyanto, Wiyanto (JURNAL PEMBELAJARAN FISIKA, 2025)
Computational thinking ability has become one of the primary focuses in science education, including physics, as a response to the challenges of the Fourth Industrial Revolution. Integrating computational physics concepts into learning requires relevant and comprehensive assessment tools to measure students' abilities. A programming-based test instrument using Scratch was designed to evaluate computational thinking skills through programming activities linked to physics principles. This study aims to develop a Scratch-based test instrument to assess students’ computational thinking abilities on the topic of sound waves within secondary-level physics education. The research employs a development method based on the stages outlined by Borg & Gall, which include: (1) analysis of potential and problems; (2) data collection; (3) product design; (4) design validation and revision; (5) product trials; and (6) data analysis and reporting of results. The trial subjects involved 99 students. The developed test instrument consists of 21 items. Based on the content validity test, 87.55% was obtained, indicating the instrument’s feasibility. The instrument's reliability was measured using Cronbach's Alpha coefficient, yielding a value of 0.781, which falls into the high category. Overall, this Scratch-based computational physics test instrument is declared suitable for evaluating students' computational thinking abilities with physics content.